Eventos extremos de precipitação : identificação e análise da bacia hidrográfica do Rio Jundiaí, São Paulo - Junior Ruiz Garcia; Bruno César Brito Miyamoto; Alexandre Gori Maia (Confins)
Global climate change may increase the variability associated with the duration, intensity, and location of extreme precipitation events. Water resource management tends to be more dependent on the knowledge about the local effects of these phenomena. In 2014, the state of São Paulo experienced one of the most intense droughts ever recorded, which affected water availability. Therefore, the main objective is to evaluate how the Jundiaí River Basin, which contemplates one of the major economic regions of the state of São Paulo, has suffered from the occurrence of extreme precipitation events. To meet this objective, precipitation data for the period 1961-2014 were used to calculate the Standardized Precipitation Index (SPI). The main results highlights: increase in precipitation volume in the recent years, except for 2014; concentration of extremely rainy years between 2009 and 2012; tendency to increase the occurrence of excess precipitation events in the long term based on SPI analyzes. Based on the SPI analyzes, there is a long-term tendency to increase the occurrence of excessive precipitation events. Society must learn to adapt to natural climate variability, which includes environmental policies for mitigation and adaptation to extreme climate events.